2019
DOI: 10.1186/s12887-019-1563-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cow’s milk-related symptom scores in early identification of cow’s milk protein allergy in Chinese infants

Abstract: Background The diagnosis of cow’s milk protein allergy(CMPA) may be easily misdiagnosed due to its lack of specific symptoms. Thus, experts have proposed the use of Cow’s milk-related symptom scores (CoMiSS) to predict CMPA. There has been no relevant report on the clinical application value of CoMiSS in Chinese children. This study aimed to evaluate the effect of CoMiSS in early identification of CMPA in Chinese infants. Methods We calculated CoMiSS for 38 infants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 11 publications
(14 reference statements)
4
58
1
3
Order By: Relevance
“…13,14 In these studies, infants suspected with CMPA were evaluated in paediatric gastroenterology clinics where patients with bloody stools and slow weight gain were also included, and no cut-off value was used regarding CoMiSS. 13,14 In another study by Prasad et al, 84.3% of the children were diagnosed with CMPA using CoMiSS with a cut-off value of ≥12, but the design of this study is quite different from ours. 15 In our study, using SBS ≥12 as the cut-off value and with a challenge test, 54.2% of the infants were diagnosed with CMPA.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In these studies, infants suspected with CMPA were evaluated in paediatric gastroenterology clinics where patients with bloody stools and slow weight gain were also included, and no cut-off value was used regarding CoMiSS. 13,14 In another study by Prasad et al, 84.3% of the children were diagnosed with CMPA using CoMiSS with a cut-off value of ≥12, but the design of this study is quite different from ours. 15 In our study, using SBS ≥12 as the cut-off value and with a challenge test, 54.2% of the infants were diagnosed with CMPA.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this study concluded that the CoMiSS™ may be useful in the diagnosis of CMA. However, they suggested that a CoMiSS™ cutoff score of ≥12 as the criterion for the early identification of CMA may be significantly high and suggested a cut-off of ≥6, at least in Chinese infants [7]. A single-blinded, prospective, multicenter trial involving infants that is validating the sensitivity and specificity of the CoMiSS™ against open oral food challenge is ongoing [8].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…23 Three studies demonstrated high risk of index test interpretation bias, due to the lack of pre-specified threshold criterion for a positive screen and a lack of blinding to the results of the reference standard. 7,23,24 All six studies were at high risk of bias in the reference standard domain because the reference standard DBPCFC was not used, while, one study included the index test in the reference standard. 25 Five studies scored high risk of bias for flow and timing; one left an interval of up to 3 months between applying CoMiSS TM and conducting OFC, 25 two excluded eligible infants from the analysis, 7,23 and two used different reference standards to establish CMPA.…”
Section: Development and Piloting Studiesmentioning
confidence: 99%
“…Seven studies received funding from the pharmaceutical or milk formula industry. 13,23,24,[27][28][29][30] Main findings…”
Section: Development and Piloting Studiesmentioning
confidence: 99%
See 1 more Smart Citation